Botulinum toxin injections for blepharospasm prior to ocular surgeries - Kaydu E (Dove Medical Press, 2012)
Seydi Okumus1, Erol Coskun1, İbrahim Erbagci1, M Gürkan Tatar2, Aysegul Comez1, Erdal Kaydu1, Ramazan Yayuspayi1, Bulent Gurler11Department of Ophthalmology, University of Gaziantep, 2Ophthalmology Clinic, Nizip State Hospital, Nizip, Gaziantep, TurkeyPurpose: The aim of this study was to show the efficiency of preoperative botulinum toxin A (Botox A) in patients with benign essential blepharospasm who were to undergo ocular surgery with local anesthesia.Materials and methods: Twenty-eight benign essential blepharospasm patients who were administered unilateral Botox A prior to ocular surgery between January 2004 and May 2011 were included in this study. Eleven cases had pterygiums, ten had cataracts, and four had glaucomas, while the remaining three had aphakia. All cases’ severity of spasm (stage 0–4) and eyelid closing forces (stage 1–4) were evaluated according to the Jankovic scale prior to the injection, at 3 days, 14 days, 1 month, and 3 months after Botox A injection.Results: Of the patients enrolled in the study, 16 were female and 12 were male, with an average age of 55.52 ± 1.53 years (52–65). Average onset of the Botox injection's effect was 2.8 ± 0.9 (2–5) days. Its effect lingered for about 11.5 ± 3.6 (8–22) weeks. The severity of spasm and eyelid closing forces of all the patients enrolled were compared prior to the injection at 3 and 14 days and the first and third months after the injection. There were statistically significant differences between prior to the injection and 3 days (P = 0.001), 14 days (P < 0.001) and 1 month after the injection (P <0.001). There was no statistically significant difference between prior to the injection and 3 months after the injection (P = 0.513). Fourteen days following the injection, the surgeries were successfully performed.Conclusion: Botox A administered prior to ocular surgery will control both blepharospasm and lower the risks that can be encountered before and during surgery, thus increasing the comfort of the patient and the surgeon.Keywords: botulinum toxin A, blepharospasm, ocular surgery